THE FREQUENCY OF POOR ENGRAFTMENT AFTER ALLOGENEIC HEMATOPOIETIC STEM CELL TRANSPLANTATION - Peulić, Nikola; Todorovic Balint, Milena; Lemajic, Nikola (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: Poor engraftment represents one of the possible complications after allogeneic hematopoietic stem cell transplantation (allo-HSCT). It presents as pancytopenia or bicytopenia, with or without complete donor chimerism. There are three entities of poor engraftment: poor graft function (PGF), graft failure (GF), and graft rejection (GR).Aim: This study aims to show the frequency of poor engraftment, as well as the frequency of all of its entities individually, among the patients of the Clinic of Hematology of the University Clinical Center of Serbia (UCCS), who underwent allo-HSCT between December 20, 2017 and December 25, 2020, for the purpose of achieving improved management and understanding of this serious complication.Materials and methods: This retrospective cohort study included 58 patients. Diagnosis of poor engraftment was confirmed by pancytopenia (cut off values: hemoglobin < 70g/L; platelet count < 20 x 109/L; absolute neutrophil count (ANC) < 0.5 x 109/L), for three consecutive days, as of day D+28, with the exclusion of severe graft versus host disease (GvHD) and relapse, with complete donor chimerism in PGF and with incomplete donor chimerism in GF. GR presented as acute rejection of the graft by the recipient with bone marrow aplasia or pancytopenia. Results: Poor engraftment was confirmed in 13 of 58 patients (22.4%). Patients with PGF were the majority, with 12.1% (seven patients), while patients with GF and those with GR had the same incidence of 5.2% (three patients). Overall survival for patients with poor engraftment after allo-HSCT was five months, which is significantly less than the overall survival of the patients who had good engraftment after allo-HSCT (57 months).Conclusion: The three types of poor engraftment must be precisely discriminated and diagnosed in relation to donor chimerism in order to decrease morbidity and mortality in patients, post allo-HSCT.
Keywords: poor graft function; graft failure; graft rejection; allo-HSCT